2006
DOI: 10.1152/ajpheart.01303.2005
|View full text |Cite
|
Sign up to set email alerts
|

Temperature modulates P2X receptor-mediated cardiovascular responses to muscle afferent activation

Abstract: Static muscle contraction increases ATP release into the muscle interstitial space. Elevated ATP in muscle stimulates thin fiber muscle afferents and increases blood pressure via engagement of purinergic P2X receptors. In addition, ATP activates P2X receptors and enhances cardiovascular responses induced by stimulation of muscle mechanoreceptors. In this study, we examined whether elevated muscle temperature would attenuate and whether reduced temperature would potentiate P2X effects on reflex muscle responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
(61 reference statements)
3
16
0
Order By: Relevance
“…In case of the P2X receptor, it has been shown that decreases in temperature increases P2X activity (148). In other words, an increased muscle temperature will decrease P2X activity and this would suggest that higher muscle temperatures might attenuate muscle reflexes (94). In contrast, increases in temperature increase the TRPV1 receptor activity (313), which would suggest that hyperthermia will facilitate muscle reflex responses to a given metabolic response.…”
Section: Peripheral Feedback From Musclesmentioning
confidence: 99%
“…In case of the P2X receptor, it has been shown that decreases in temperature increases P2X activity (148). In other words, an increased muscle temperature will decrease P2X activity and this would suggest that higher muscle temperatures might attenuate muscle reflexes (94). In contrast, increases in temperature increase the TRPV1 receptor activity (313), which would suggest that hyperthermia will facilitate muscle reflex responses to a given metabolic response.…”
Section: Peripheral Feedback From Musclesmentioning
confidence: 99%
“…a,b-MeATP evokes reflex cardiovascular responses in muscle microvessels, via P2X receptors, when injected into the arterial supply of the cat hindlimb vasculature (Li and Sinoway, 2002;Hanna et al, 2002;Gao et al, 2006). P2X receptors can produce vasoconstriction in exercising canine skeletal muscle (Buckwalter et al, 2003(Buckwalter et al, , 2004.…”
Section: Skeletal Muscle Microvasculature and Femoral Arterymentioning
confidence: 99%
“…The effect of P2X receptor on reflex muscle response has recently been reported to be sensitive to alternations of T m (Gao et al, 2006). This prior study further suggests that elevated T m attenuates the pressor response to static muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Contractions induced by electrical stimulation of the sciatic nerve were then performed in nine healthy control rats and 10 MI rats. Static contraction of the triceps surae muscle was conducted at frequencies of 30 Hz (2.5 times motor threshold and 0.1 ms duration; Gao et al, 2006). Stimulation was sustained for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation